A novel approach for the closure of large damage in self-healing elastomers using magnetic particles. (9th September 2020) - Cerdan, Kenneth; Van Assche, Guy; van Puyvelde, Peter; Brancart, Joost
Abstract: Self-healing materials have been intensively studied as materials that can mimic healing properties of biological systems. Reversible polymer networks based on Diels-Alder thermoreversible covalent bonds exhibit great healing performance by controlling the temperature of the system. Despite the attractive applications of self-healing materials, most of them are restricted to the repair of narrow cracks due to their restricted mobility in the solid state. In this work, magnetite (Fe3 O4 ) particles are used to create self-healing magnetic composites. The use of a conventional magnet to apply a magnetic driving force is proposed for the closure of wide damage gaps in the solid state without the need of either mechanical intervention or liquid-like flow inside the material, limiting the structural stability. Thermal, mechanical and chemical characterization of different composites are performed in this study and the healing efficiency is evaluated to assess their potential to close and heal large damage sizes. Graphical abstract: Image 1 Highlights: Synthesis and characterization of magnetic Diels-Alder thermoreversible elastomeric composites with self-healing ability. The effect of Fe3 O4 nanoparticles on the reaction kinetics, thermodynamics and viscoelastic behaviour of the formed composites. Magnetic composites experience damage gap closure under the application of an external magnetic field. Optimum in filler loading between magnetic response and healing efficiency.